FAKTOR - FAKTOR YANG MEMPENGARUHI FIRM PERFORMANCE PADA PERUSAHAAN MANUFAKTUR - Dianti Anindya Putri, Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empiricial evidence about the effects of liquidity, capital structure, asset structure, inventory turnover, and cash turnover on firm performance in manufacturing company listed in the Indonesian Stock Exchange in the period of 2016-2018. The research is conducted by taking sample of 70 manufacture company. The t-test shows that there are negative relation between capital structure and asset structure on firm performance. While inventory turnover has positive relation with firm performance. However there is no significant relation liquidity dan cash turnover on firm performance.